ADSORPSI FENOL OLEH ARANG AKTIF DARI AMPAS KOPI - Nisa Hayatun Nufus Sunandar; Teguh Wirawan; Rahmat Gunawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2012)
The comparison of phenol adsorption with activated carbon from coffee residue has been conducted. The first step in this study is coffee residue activation with ZnCl2 in 85oC during 7 hours. The coffee residue was dryed in 24 hours at 110oC and after that it was dissolved by activated carbon with 10% HCl and pH neutralized by using aquades 65oC. The activated carbon was determinate at pH 2-6, with time 15-60 minutes and phenol concentration 2-10 mg/L. From that result would be processed with isotherm Freundlich’s equation. The optimum conditions result obtained at pH 4, time 30 minutes and adsorption capacity of 1.733 mg/g. The activated carbon has been used into waste samples which have addition of phenol and obtained result 2.4751 mg/L from 6.4778 mg/L for waste water A. W. Sjahranie hospital and 0.0560 mg/L from 2.0068 mg/L for Karang Mumus River.Keywords: Phenol, adsorption, activated carbon, coffee residue